Low attendance of university students in theoretical lectures and it's relation with some variables “A Field Study at Tishreen University” - صالح, غسان; حمدان, ميساء; بوبو , منذر; القاضي, لمى; يوسف, سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aims to investigate the factors affecting the low attendance of university students in theoretical lectures and its relation with many variables such as gender, year of study, type of faculty, work, and residence. For that, the descriptive method was used, and a questionnaire of the factors affecting the low attendance was prepared. The simple random sample consisted of 2467)) male and female students was chosen from the medical faculties, Engineering, Economics, Literatures, Science, and Educational Science at Tishreen University. The results showed that the factors affecting the low attendance of university students are attributed to economical – social factors, student, teacher, curriculum, administration, and extra factors. In addition, there were no significant differences in low attendance due to sex, while there were significant differences due to year of study in the favor of last years of study. It also showed significant differences due to the type of college in low attendance in the favor of applied college, and residence variable affects the low attendance in favor of students who residents out of city. There were significant differences due to work in low attendance in the favor of students who work in governmental job. In the light of the results of this study, the research recommended the necessity of the development of university infrastructure, use of new methods and workshop, and providing universal residences for development of learning outcomes.